Inhibitory effect of Idelalisib on selenite-induced cataract in Sprague Dawley rat pups. (4th March 2022) - Zhang, Ruotong; Wei, Yiying; Zhang, Shanshan; Li, Hailong; Li, Jinhe; Ma, Bowei; Zhu, Xiaoqing; Song, Xudong; Zhou, Honggang
ABSTRACT: Purpose: The aim of this study was to evaluate the therapeutic effect of Idelalisib, Apelisib and Copanlisib on 8-day-old cataract SD rat pups. Materials and methods: The rat model induced by sodium selenate (Na2 SeO3 ) was used in this study. Experimental animals were randomly divided into five groups with eight animals in each group. They were control group, Na2 SeO3 group, Idelalisib group, Apelisib group and Copanlisib group. On days 3, 5 and 7, all rats in Na2 SeO3, Idelalisib, Apelisib and Copanlisib groups were given subcutaneous injection into the nape with Na2 SeO3 and control group was given the same amount of saline. For days 1-14, Idelalisib, Apelisib and Copanlisib were given by intragastric administration, respectively, and the same amount of saline was given to the control group and Na2 SeO3 group. On the 15th day of the experiment, we selected the Idelalisib group with the best effect from all groups, separated their lenses, and further analyzed the crystal proteins, oxidative damage and apoptosis indexes. Results: The survival rate of rats in control and Idelalisib groups was 100%, the Na2 SeO3 group was 37.5%, the Apelisib group was 25%, and the Copanlisib group was 0. According to the rat survival rate and lens score, we selected Idelalisib for further analysis of the crystallin, oxidative damage and apoptosis indexes. The results suggested that Na2 SeO3 leads to cataract formation and crystallin precipitation. The levels of antioxidant enzymes GSH and SOD were decreased in the Na2 SeO3 group, Nrf-2 and HO-1 were downregulated, Keap1 upregulated, and cleaved caspase-3 and Bax/Bcl-2 upregulated. Idelalisib significantly improved crystallin insolubility, reduced oxidative damage, and inhibited lens apoptosis. Conclusion: In summary, Idelalisib can significantly improve the progression of Na2 SeO3 -induced cataract in rats. In the future, it may be a potential effective drug candidate for the clinical treatment of cataract.